Intraoperative molecular imaging: 3rd biennial clinical trials update - Bou-Samra, Patrick; Muhammad, Najib; Chang, Austin; Karsalia, Ritesh; Azari, Feredun; Kennedy, Gregory; Stummer, Walter; Tanyi, Janos; Martin, Linda; Vahrmeijer, Alexander; Smith, Barbara; Rosenthal, Eben; et al. (Journal of biomedical optics, 2023)
This third biennial intraoperative molecular imaging (IMI) conference shows how optical contrast agents have been applied to develop clinically significant endpoints that improve precision cancer surgery. National and international experts on IMI presented ongoing clinical trials in cancer surgery and preclinical work. Previously known dyes (with broader applications), new dyes, novel nonfluorescence-based imaging techniques, pediatric dyes, and normal tissue dyes were discussed. Principal investigators presenting at the Perelman School of Medicine Abramson Cancer Center's third clinical trials update on IMI were selected to discuss their clinical trials and endpoints. Dyes that are FDA-approved or currently under clinical investigation in phase 1, 2, and 3 trials were discussed. Sections on how to move benchwork research to the bedside were also included. There was also a dedicated section for pediatric dyes and nonfluorescence-based dyes that have been newly developed. IMI is a valuable adjunct in precision cancer surgery and has broad applications in multiple subspecialties. It has been reliably used to alter the surgical course of patients and in clinical decision making. There remain gaps in the utilization of IMI in certain subspecialties and potential for developing newer and improved dyes and imaging techniques.